2022
DOI: 10.3389/fcomp.2022.892597
|View full text |Cite
|
Sign up to set email alerts
|

The emotions effect on a virtual characters design–A student perspective analysis

Abstract: Interaction between people and virtual characters through digital and electronic devices is a reality. In this context, the design of virtual characters must incorporate emotional expression at a nonverbal level looking for effective communication with the user. This exploratory study investigates the design features of an avatar functioning as a virtual assistant in educational contexts. From a multidisciplinary approach, the user's research was elaborated by a semi-open questionnaire of self-perception of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Drawing inspiration from the widely recognised Godspeed questionnaire, a renowned tool for assessing users' direct impressions of their interactions with both robots and humans, the questionnaire was designed [58,59]. By utilising this established questionnaire as a foundation, the research benefited from established metrics and methodologies for evaluating users' experiences with the robot-assisted platform.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing inspiration from the widely recognised Godspeed questionnaire, a renowned tool for assessing users' direct impressions of their interactions with both robots and humans, the questionnaire was designed [58,59]. By utilising this established questionnaire as a foundation, the research benefited from established metrics and methodologies for evaluating users' experiences with the robot-assisted platform.…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggested that different VCs can elicit different emotional reactions in users; this is likely to be true in the case of human avatars in VR as well. Although further research is required to understand what types of FoB, or emotions in general, can be associated with different types of avatar VCs in multi-user VR environments, the designers of such avatars can already consider the emotional engagement in the design process by considering previous research related to emotional design of virtual characters (e.g., [17,42,43]).…”
Section: Implications Of the Findingsmentioning
confidence: 99%